Remote learning tool as method of students' assesment in discipline "Dermatology. Venerology" - Hulei, Liliia Omelyanivna; Malkovych, Nataliia Mykolaivna (Journal of Education, Health and Sport, 2020)
In recent months, medical education has changed dramatically and many medical educational institutions all over the world have been started to expand modern training methods, for the coronavirus disease 2019 (COVID-19) pandemic. Purpose of the research was to evaluate the foreign students' knowledge of the medical faculty №3, in fourth year education and prepare them for taking successfully the final module control in the discipline "Dermatology. Venereology" in the Bukovinian State Medical University (Chernivtsi,Ukraine) by using the contemporary learning tool Classmarker.